Diagnosis of carbon footprint in the generation of solid waste in the production of agroindustrial training center "La Angostura" units - Camacho, Juan David
The carbon footprint is an indicator that measures the production of greenhouse gases (GHG) generated by the various activities of individuals, companies, events, among others by conducting an inventory. It is relevant to develop this project at the Agroindustrial Training Center “La Angostura” (CEFA) as it allowed us to know and evaluate the impact of greenhouse gas emissions generated by the various activities performed routinely in the productive units (UP in its Spanish acronym). For this project, a diagnosis of the carbon footprint was undertaken in the 10 UP located in several productive areas such as livestock, agricultural crops, and natural environments at CEFA. To develop this diagnosis, routine activities were identified and described in the units, determining emissions sources of GHG thereby allowing for the scope of the gases emitted by the activities in UP to be established, these processes helped identify the productive units that generated emissions of greater impact on the atmosphere. Identification and quantification of solid waste generated weekly (weight in kg) in the productive units and areas for one month were conducted, the records were consolidated into one GEH 2015 spreadsheet of the Catalan Climate Canvil office, which allowed to estimate the number of tons of carbon dioxide equivalent (CO2e TON), and estimate the contribution of carbon footprint of CEFA. It was found that the area with the greatest contribution to the carbon footprint is the livestock area, with 91% of CO2eq production generated by livestock units (18% CO2 eq) and the unit of pigs farming (72% CO2eq). This project is expected to raise public awareness with the goal of establishing mitigation strategies based on corrective and preventive measures.